Toxic heavy metals in groundwater of a portion of the Front Range mineral belt - Edwards, Kenneth W., 1928-, author; Klusman, Ronald W., author; Environmental Resources Center, Colorado State University, publisher (Colorado State University. Libraries, 1975)
Anodic stripping voltammetry and gas chromatography have been investigated with respect to their suitability for multielement analyses of trace elements in natural waters. The elements of interest in this study of toxic and esthetically undesirable elements in the regional ground waters of the Front Range Mineral Belt are arsenic, cadmium, copper, iron, lead, manganese, mercury, selenium, silver, and zinc. Atomic absorption spectrophotometry is commonly used for analysis of these elements but permits only one element to be determined at a time. Anodic stripping voltammetry was found to be highly sensitive and suitable for determination of low concentrations of cadmium, copper, lead, manganese, and mercury. For most of these elements the reproducibility was excellent at the ppb concentration level. Compared with direct flame atomic absorption, this method was found to be more sensitive but not significantly faster despite determination of several elements per analysis. Gas chromatography was investigated for analysis of arsenic, antimony, and selenium by generation and separation of their hydrides. The method was found to be difficult to use effectively and not sufficiently sensitive for natural water analysis.
Front Range Mineral belt
Keywords: Water quality -- Colorado -- Clear Creek Watershed; Trace elements -- Toxicology; Mineralogical chemistry; Groundwater -- Pollution -- Colorado -- Clear Creek Watershed; Heavy metals